Integrasi Tradisi Batobo dalam Pembelajaran IPS di SMP Negeri 29 Sijunjung: The Integration of Batobo Tradition into Social Studies Learning at SMP Negeri 29 Sijunjung - Dola Anggraini (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2025)
This study aims to explore how the values of the Batobo tradition can be integrated into social studies learning at State Junior High School 29 Sijunjung. This is intended to enhance students' social attitudes. The study employs a qualitative approach with a case study method. The research informants include Social Studies teachers and students. Data were collected through observation, interviews, and documentation. Data analysis was conducted using an interactive model, which includes data reduction, data display, and conclusion drawing. The findings of this study indicate that the Batobo tradition, which emphasizes cooperation, mutual assistance, solidarity, and social responsibility, can serve as an effective medium for contextual Social Studies learning. This study introduces the integration of local wisdom-based Social Studies learning to strengthen students' character.